Lignin extraction distinctively enhances biomass enzymatic saccharification in hemicelluloses-rich Miscanthus species under various alkali and acid pretreatments. (May 2015) - Si, Shengli; Chen, Yan; Fan, Chunfen; Hu, Huizhen; Li, Ying; Huang, Jiangfeng; Liao, Haofeng; Hao, Bo; Li, Qing; Peng, Liangcai; Tu, Yuanyuan
Highlights: One-step pretreatment with 4% NaOH has the highest hexoses yields in Miscanthus . 2% NaOH followed by 1% H2 SO4 is optimal for high biomass saccharification. Hemicelluloses-rich Miscanthus samples show largely enhanced biomass digestibility. Lignin extraction predominately determines hexoses yields upon various pretreatments. Suggest the potential applications in energy crop breeding and biomass process. Abstract: In this study, one- and two-step pretreatments with alkali and acid were performed in the three Miscanthus species that exhibit distinct hemicelluloses levels. As a result, one-step with 4% NaOH or two-step with 2% NaOH and 1% H2 SO4 was examined to be optimal for high biomass saccharification, indicating that alkali was the main effecter of pretreatments. Notably, both one- and two-step pretreatments largely enhanced biomass digestibility distinctive in hemicelluloses-rich samples by effectively co-extracting hemicelluloses and lignin. However, correlation analysis further indicated that the effective lignin extraction, other than the hemicelluloses removals, predominately determined biomass saccharification under various alkali and acid pretreatments, leading to a significant alteration of cellulose crystallinity. Hence, this study has suggested the potential approaches in bioenergy crop breeding and biomass process technology.